Analysis of transmission expansion planning considering consumption-based carbon emission accounting. (1st May 2017) - Sun, Yanlong; Kang, Chongqing; Xia, Qing; Chen, Qixin; Zhang, Ning; Cheng, Yaohua
Highlights: Calculation of virtual carbon emission flow and consumption side carbon emission. Transmission planning towards equity of consumption side carbon emission. Equity index of consumption side carbon emission to quantify transmission planning. Abstract: Consumption-based carbon emission accounting is able to clarify consumers' responsibility for the carbon emissions from a power system. The responsible amount of carbon emissions for each consumer can be calculated based on the power consumption and the accordant carbon emission flow (CEF). Distribution of the CEF in the network may vary significantly under different transmission network configurations, resulting in different attributed carbon emission responsibilities of consumers. This paper describes how transmission expansion planning (TEP) and consumption-based carbon emission accounting affect each other. A novel TEP model considering the consumption-based carbon emission accounting is presented. A new index named CO2 allocation equity coefficient (CAEC) is introduced to quantify the equity performance of the consumption-based carbon emission accounting system. As such, the requirement for different equity performances can be explicitly incorporated into the TEP model as a constraint to determine its effect on TEP. The proposed TEP model is tested on Garver's 6-bus system and a modified IEEE 39-bus system. The results show that the methodology is able to obtain the transmission expansion planning, in general, more lines must be planned to achieve better equity performance, with more even consumption-based carbon emission, but leading to an overall increasing tendency in the annualized transmission investment cost.